Osmanlı Maârifi’nde okutulan mûsikî kitaplarınaiki örnek : medhal-i mûsikî ve telhîs-i mûsikî (metin inceleme) - Çamlı, Şahin (My University, 2014)
OSMANLI MAÂRİFİ’NDE OKUTULAN MÛSİKÎ KİTAPLARINA İKİ ÖRNEK: MEDHAL-İ MÛSİKÎ VE TELHÎS-İ MÛSİKÎ (Metin İnceleme) Osmanlı’da XVIII. yy.da başlayan reform hareketleri eğitimde de yansımasını bulmuş, ülkenin her yerinde Batılı anlamda okullar açılmaya başlanmıştır. Mûsikî derslerinin bu okulların müfredatında yer edinmesiyle birlikte bu dersler için kaynak ihtiyacı da doğmuştur. Pek çoğu mûsikî muallimlerince yazılan ve Maârif Nezâreti onayıyla basılan kitaplardan ikisi Medhal-i Mûsikî ve Telhîs-i Mûsikî’dir. Çalışmamızın amacı Sâhibzâde Mehmed Şevket Efendi’ye aid bu iki eseri o dönemin ışığında ele almak ve transkripsiyonunu yapmaktır. Nezâreti, Sâhibzâde Mehmed Şevket,

TWO EXAMPLES TO THE MUSIC BOOKS HANDLED IN THE OTTOMAN EDUCATION: ENTRANCE OF THE MUSIC AND SYNOPSIS OF THE MUSIC (Analysing the Text) The reform movements that occured in the XVIII. century in the Ottoman Empire, had a reflection on education and there began opening schools which had styles of the west. When the musical lessons took place in these shools’ education system, there occured a need to the sources for these lessons. The Entrance to the Music and the Synopsis of the Music are the two example to these books; most of, written by music lecturers and published with the aproval of the Ministry of Education. The aim of our work is, to handle and transcribe these two works belonging to Sâhibzâde Mehmed Şevket Efendi within the light of that time. stry of Education, Sâhibzâde Mehmed Şevket, Music Books
Keywords: Eğitim ve Öğretim; İslam Dini; Müzik; Tarih; Türkiye